A dyadic genotype–phenotype approach to diagnostic criteria for Proteus syndrome. Issue 4 (6th November 2019) - Sapp, Julie C.; Buser, Anna; Burton‐Akright, Jasmine; Keppler‐Noreuil, Kim M.; Biesecker, Leslie G.
Abstract: Phenotype‐based diagnostic criteria were developed for Proteus syndrome in 1999 and updated in 2006. Subsequently, the causative mosaic gene alteration was discovered, the c.49G>A p.E17K variant in AKT1 . As well, a number of overlapping overgrowth disorders attributable to mosaic PIK3CA variants have now been characterized, leading to the designation of PIK3CA ‐related overgrowth spectrum (PROS). Finally, ongoing work to better characterize Proteus syndrome has led to identification of additional features of that disorder that could be useful in diagnostic criteria. We have taken the opportunity of these discoveries to re‐evaluate the Proteus syndrome diagnostic criteria. Here we propose a new set of diagnostic criteria that establishes a weighted, point‐based system for the phenotypic attributes and then integrates that with the potential molecular test results to result in one of two designations: AKT1 ‐related Proteus syndrome or AKT1 ‐related overgrowth spectrum. A patient whose only manifestation is an AKT1 c.49G>A‐positive tumor would receive neither of these designations. Here we review the rational basis of diagnostic criteria and argue that a unitary diagnostic entity is a distinct gene‐phenotype dyad and that this should be the model for all mendelian disorders. The gene‐alone or phenotype‐alone approach is inadequate to rigorously delineate a unitary diagnostic entity.